Pengaruh pergantian manajemen, opini audit, financial distress, dan ukuran KAP terhadap auditor switching - rizqiyah, wasiatur (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to examine the effect of management change, audit opinion, financial distress, and KAP size on auditor switching. The research method used is quantitative method. The data in this study uses secondary data in the form of annual reports from companies engaged in Real Estate & Property from 2016 - 2020 which are listed on the IDX. The data collection process was carried out using purposive sampling method and obtained 20 companies that were sampled, and used logistic regression as a data analysis technique. The results of this study indicate that there is an effect of management change, audit opinion, and KAP size on auditor switching, while the financial distress variable has no effect on auditor switching.